Effect of Behavioral Anomalies in Investment Decisions of Investors in Nepalese Capital Market - Adhikari, Pitri Raj; Gautam, Srijana (The Journal of Economic Concerns, 2025)
The study examines the effect of behavioral anomalies on the investment decisions of Nepalese capital market investors using a closed-end questionnaire as primary data collection method. By analyzing a sample of 504 respondents, the research investigates the influence of six behavioral anomalies: overconfidence, representativeness, herding, anchoring, loss aversion and confirmation. The study has used both descriptive and casual comparative research designs. The findings reveal that investors are not rational, and there is a significant impact of different behavioral anomalies, particularly overconfidence, representativeness, herding, and anchoring on the investment decisions of investors in Nepal. These results suggest that behavioral anomalies can significantly affect the investment decisions of Nepalese investors and may have negative consequences for their investment outcomes. The study recommends that investors be aware of these anomalies and take measures to reduce the impact on decision-making.